2015
DOI: 10.1016/j.bbrc.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of myosin II regulatory light chain by ZIP kinase is responsible for cleavage furrow ingression during cell division in mammalian cultured cells

Abstract: Zipper-interacting protein kinase (ZIPK) is known to regulate several functions such as apoptosis, smooth muscle contraction, and cell migration. While exogenously expressed GFP-ZIPK localizes to the cleavage furrow, role of ZIPK in cytokinesis is obscure. Here, we show that ZIPK is a major MRLC kinase during mitosis. Moreover, ZIPK siRNA-mediated knockdown causes delay of cytokinesis. The delay in cytokinesis of ZIPK-knockdown cells was rescued by the exogenous diphosphorylation-mimicking MRLC mutant. Taken t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Therefore, we examined whether the MRLC isoforms actually served as kinase substrates because MRLC phosphorylation causes myosin II activation [Ikebe and Hartshorne, ; Ikebe, ]. Each purified MRLC was incubated with human ZIP‐kinase, which is known to be a representative kinase for MRLC at Thr18/Ser19 [Murata‐Hori et al, 1999, 2001; Hosoba et al, ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we examined whether the MRLC isoforms actually served as kinase substrates because MRLC phosphorylation causes myosin II activation [Ikebe and Hartshorne, ; Ikebe, ]. Each purified MRLC was incubated with human ZIP‐kinase, which is known to be a representative kinase for MRLC at Thr18/Ser19 [Murata‐Hori et al, 1999, 2001; Hosoba et al, ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a reduction in focal adhesion kinase (FAK) activity by the ectopic expression of DAPK3 (Nehru et al, 2013) may contribute to cell adhesion regulation during epithelial wound repair with impacts on IEC proliferation and survival (Owen et al, 2011). The augmentation of MLC20 phosphorylation by DAPK3 stimulates actomyosin contraction and cleavage furrow ingression (Hosoba et al, 2015), which are important for cytokinesis during cell division (Ono et al, 2020). Finally, the presence of a loss-of-function DAPK3 mutant Asp161Asn was associated with cytokinesis failure and could induce multinucleation via decreased actomyosin phosphorylation at the contractile ring in CRC cells (Ono et al, 2020).…”
Section: Potential For Dapk3 Involvement In Epithelial Wound Repairmentioning
confidence: 99%
“…Previous studies have reported that death-associated protein kinase 3 (DAPK3), also known as ZIPK, directly phosphorylates MYL9 and regulates the actomyosin contraction in vascular smooth muscle via MYL9 phosphorylation [15,16]. In addition, recent studies have shown that DAPK3 also regulates cleavage furrow ingression in cytokinesis [17][18][19].…”
Section: Introductionmentioning
confidence: 99%